(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2022)
How do we make sense of the global and granular at the same time? This visual essay explores the relationship of the macro and micro through everyday practices of image making, cropping, and sharing. It asks whether new ways of knowing emerge or if perhaps patterns of sensemaking pre-exist, a psychological or social equivalent to fractals in nature. This becomes relevant when we consider that it is precisely within the mundane details of everyday actions of sensemaking that future structures are born. In wonders about how, in times of global trauma, might these micro practices reinforce or resist existing relations among humans, technologies, and the planet.